An Anatomy of Marginality: Figures of the Eternal Return and the Apocalypse in Chilean Post-Dictatorial Fiction - Idelber Avelar (Studies in 20th & 21st Century Literature, 1999)
The article analyzes two novels by Chilean writer Diamela Eltit from the standpoint of the post-dictatorial imperative to mourn the dead and reactivate collective memory. After framing Eltit's fiction in the context of the avant-garde resurgence of plastic and performance arts in the second half of Pinochet's regime, I move on to discuss Lumpérica (1983) and Los vigilantes (1994) as two different manifestations of the temporality of mourning. The article addresses how Lumpérica's portrayal of an oneiric, orgiastic communion in marginality (shared by the protagonist and a mass of beggars at a Santiago square) composed an allegory in the strict Benjaminian sense; it further notes how such allegory, as an anti-dictatorial, oppositional gesture, could only find a home in a temporality modeled after the eternal return. I then show how Los vigilantes, a post-dictatorial novel centered on the task of mourning, abandons the circular logic of the eternal return in favor of an eschatological, finalist matrix of an apocalyptic type. Eltit's shift—which I present as a move from an affirmation of impossibility to the impossibility of affirmation—is not presented merely as a personal matter of choice, but as an expression of a predicament proper to post-dictatorial fiction.
Keywords: Chilean literature; Diamela Eltit; post-dictatorship; mourning; collective memory; avant-garde; plastic arts; performance arts; Pinochet; Lumpérica; Los vigilantes; temporality of mourning; temporality; marginality; opposition; post-dictatorial fiction